A practicum at Euro-Swiss Food Incorporated San Antonio, Makati City - Misoles, Lorilie Matobato (2006)
Euro-Swiss Food, Inc. (ESFI) is known for its highly prestigious image in the meat processing and the hotel and restaurant industry. For two decades, it has constantly provided its customers with high quality products and has simultaneously improved its manufacturing system. Despite of the company?s continuous growth and success, it is still geared toward further technical improvements and production expansions. The currently adapted operational steps in the production of meat products have been subjected to thorough assessment through a practicum on April to May 2005. The manufacturing plant?s lay-out, facilities, equipment, raw material inventory, food processing line, food quality assurance and safety, waste management and by-product utilization, labor and human resource management, and overall food processing management were the specific areas observed. The major recommendations include the following establishment of a quality control/quality assurance department, conduct microbial and chemical tests for effective wastewater management, elimination of smoking area, renovation of comfort room and/or changing room, development of flavor formulation and intensive documental for all operations, the materialization of a HACCP system and strict implementation of GMP will also be greatly beneficial for the company